MAIT cells regulate NK cell-mediated tumor immunity - Emma V. Petley (Nature Portfolio, 2021)
Mucosal-associated invariant T (MAIT) cells facilitate anti-microbial responses, but their functions in cancer protection is unclear. Here the authors show that activated MAIT cells induce an IFN-γ transcriptome in natural killer (NK) cells and enhance NK-dependent anti-cancer immunity in mice, thereby hinting a new avenue for cancer therapy.